Managing in the public sector - Blundell, Brian; Murdock, Alexander ([S.l.] : Butterworth-Heinemann, 1997)
Managing in the Public Sector first presents a sound theoretical framework and then helps the reader translate this into competent management performance. It is written in a highly accessible style and is illustrated with practical case examples drawn from a variety of settings. The reader is encouraged to continue their development through graded action planning and further reading. The book is based upon the Management Charter Initiative's Occupational Standards for Management NVQs and SVQs at Levels 4 and 5 and is also particularly suitable for managers on Certificate and Diploma in Management Programmes, including those accredited by the IM and BTEC. It will be particularly relevant to managers in the Civil Service/Next Steps Agencies, Local Government, Health and Social Services, the Police Service, the Fire Service, and the Voluntary and Private Sector organizations providing public services. Managing in the Public Sector is part of the highly successful series of textbooks for managers which cover the knowledge and understanding required as part of any competency based management programme. The books cover the three main levels of management: supervisory/first-line management (NVQ level 3), middle management (Certificate/NVQ level 4), and senior management (Diploma/NVQ level 5). Alex Murdock is Principal Lecturer in Public Service Management at South Bank University Business School and Brian Blundell is an organizational research and learning consultant with a special interest in the Health Service. Endorsed by the Institute of Management Competence based and ideal for managers in all areas of the Public Sector working for the NVQ Level 5 management qualification. Public Sector Management covered in some depth on most traditional management courses, notably the BTEC Diploma and all MBA courses.
Keywords: management,public sector